Early Marriage from the Perspective of Jurisprudence and Adolescent Psychology - Ririn Yulis (Al-Fiqh: Journal of Contemporary Islamic Law, 2025)
This study aims to examine the phenomenon of early marriage from two main perspectives: Islamic jurisprudence and adolescent psychology. In Islamic jurisprudence, early marriage is often justified as long as it meets the requirements and pillars, but, psychologically, adolescence is considered a transitional period that is not yet emotionally or cognitively stable. This study uses a qualitative approach, drawing on literature on classical and contemporary Islamic jurisprudence and adolescent developmental psychology. The results of the study indicate that although Islamic jurisprudence does not explicitly prohibit early marriage, there are principles of maslahah (benefit) that require mental, emotional, and economic readiness before marriage. From a psychological perspective, marriage at a young age poses a risk to relationship stability due to immature communication skills, conflict resolution, and emotional control. The implications of this study emphasize the importance of an integrative approach to addressing early marriage, namely by considering both Islamic law and adolescent psychological readiness simultaneously. These findings can serve as a reference for educators, parents, and policymakers in providing more holistic, context-specific marriage education.